Chingkhui: Pengembangan Ekonomi Kelompok Perempuan Teumareum - Hary Elta Pratama; Nur Rohman Dolok Saribu; Aalia Letiara Trisilia; Sartika Rahayu; Umi Saputri; Gea Ramadhani; M. Aulia Rahman; Teuku Jumadil Aulia; Fadjar Siddiq; Ridwan (Jurnal Riset dan Pengabdian Masyarakat, 2023)
Chingkhui is one of the traditional food ingredients in Indra Jaya District. This chingkhui powder development business, if carried out professionally, by paying attention to shape innovation, flavor strengthening, packaging and market strategy, will eventually be able to compete with modern food and will provide good opportunities and potential to be developed so that it will bring benefits as well as become a promotional event for traditional foods. Seeing the potential that exists, the community, especially the women of Teumareum Village, Indra Jaya District, Aceh Jaya Regency must develop variations of processed chingkhui powder. Technical guidance on improving the quality of business and assistance and program evaluation through the Community Service (PKM) program. The program to increase the variety of processed products was carried out by the Malay Real Work Lecture Students (KKN) of Teumareum Village in 2022 Batch III of State Islamic Religious Universities (PTKIN) throughout Sumatra-Aceh Jaya. The implementation of this program is not only carried out by KKN students, but the process of making it is also assisted by the women in Teumareum Village. The implementation of the Serumpun Melayu KKN program can help the community in this case in Teumareum Village, Indra Jaya District, Aceh Jaya Regency to increase their economic income through community empowerment of the Teumareum women's group to make higher quality products. Through the implementation of the Serumpun Malay Community Service Program, it is very helpful for the community in Teumareum Village, Indra Jaya District, Aceh Jaya Regency in terms of increasing the variety of chingkhui powder products through processed aspects of production.